El Excentrico, 1979-09-20 & 1979-10-05 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
September 20 & October 5, 1979 [20 de septiembre y 5 de octubre de 1979]. Ano 30, No 11. Cover contains an illustration of Saint Joseph, the Virgin Mary, and a baby Christ. The headline reads, Amigo Tours invita a Uds. a participar a la Gran Pereginacion Guadalupana A la Ciudad de Mexico" (transl: Amigo Tours invites you to participate in the Great Pilgramage of Guadalupe to Mexico City).